Chapter 37 The intangible made tangible in Wales - Young, Einir M. (Taylor & Francis, 2017)
This collection provides an in-depth and up-to-date examination of the concept of Intangible Cultural Heritage and the issues surrounding its value to society. Critically engaging with the UNESCO 2003 Convention for the Safeguarding of the Intangible Cultural Heritage, the book also discusses local-level conceptualizations of living cultural traditions, practices and expressions, and reflects on the efforts that seek to safeguard them. Exploring a global range of case studies, the book considers the diverse perspectives currently involved with intangible cultural heritage and presents a rich picture of the geographic, socioeconomic and political contexts impacting research in this area. With contributions from established and emerging scholars, public servants, professionals, students and community members, this volume is also deeply enhanced by an interdisciplinary approach which draws on the theories and practices of heritage and museum studies, anthropology, folklore studies, ethnomusicology, and the study of cultural policy and related law. The Routledge Companion to Intangible Cultural Heritage undoubtedly broadens the international heritage discourse and is an invaluable learning tool for instructors, students and practitioners in the field.